A critical investigation of plant optimization, to improve the production process of Mercedes-Benz commercial vehicles in South Africa. (Jan 2004 - Sept 2004) - Naidoo, Desalin Rajoo (Rhodes University, Faculty of Commerce, Investec Business School, 2005)
The research thesis reflects a positive improvement to the plant efficiency through strategic optimisation planning and controlling systems. It's important to note that the set goals of the research were achieved, with total employee buy-in contributing to the success and sustainability of these improvements. Purposive sample methods allowed for the twenty employees from a total of 172, to be interviewed for both the pre and post testing. The paradigm of the research contributed to integrative communication between brainstorming and action. The efforts of the total workforce must be commended, for strategically aligning the organizational goals and objectives to realization. The content of the thesis, show a direct relationship between the plant optimisation and the increase in the production volumes. The understanding of the downtime reports for the period specified is a direct reflection to the improvement in quality, and the reduction of the overall poor workmanship graphs indicates positively to the reduction in cost. The last value driver, on-time delivery shows a vast improvement in maintaining the customer satisfaction, when considering the increase to the production volume capacity. These improvements have made further volume increases probable, and the understanding of Ikhwezi Trucktech management to negotiate with realized information for future capacity planning.
Keywords: Automobile industry and trade -- South Africa -- Management; Motor vehicle industry -- Production control -- South Africa; Production management